Charlotte Posenenske Do Impresarios Dream of 3-D Cinema?. (1st August 2013) - Carey-Kent, Paul
Posenenske's mature output bears a superficial resemblance to Donald Judd's work, but really diverges from it in frustration over its inability to deliver social change. Yet Brunn says that though Posenenske was aware of the American trends, she came from a different place: her movement from painted illusion to geometric order may echo the minimalists, but Posenenske's real interest lay in participation.